Aspidoglossum albocoronatum (Apocynaceae, Asclepiadoideae), a new species with a remarkable petaloid corona from the northern provinces of South Africa - Bester, Stoffel P.; Nicholas, Ashley (Phytotaxa, 2016)
Aspidoglossum albocoronatum Bester & Nicholas is a unique species from Sekhukhuneland in Mpumalanga and southern Leolo Mountains in Limpopo, South Africa. In morphological character it belongs to the southern African Schizoglossum complex (which includes the genera Aspidoglossum, Schizoglossum s.s. and Miraglossum). A description, line drawings and a comparative table to its related genera are presented.